Chesapeake Bay nitrogen fluxes derived from a land‐estuarine ocean biogeochemical modeling system: Model description, evaluation, and nitrogen budgets. Issue 8 (28th August 2015) - Feng, Yang; Friedrichs, Marjorie A. M.; Wilkin, John; Tian, Hanqin; Yang, Qichun; Hofmann, Eileen E.; Wiggert, Jerry D.; Hood, Raleigh R.
Abstract: The Chesapeake Bay plays an important role in transforming riverine nutrients before they are exported to the adjacent continental shelf. Although the mean nitrogen budget of the Chesapeake Bay has been previously estimated from observations, uncertainties associated with interannually varying hydrological conditions remain. In this study, a land‐estuarine‐ocean biogeochemical modeling system is developed to quantify Chesapeake riverine nitrogen inputs, within‐estuary nitrogen transformation processes and the ultimate export of nitrogen to the coastal ocean. Model skill was evaluated using extensive in situ and satellite‐derived data, and a simulation using environmental conditions for 2001–2005 was conducted to quantify the Chesapeake Bay nitrogen budget. The 5 year simulation was characterized by large riverine inputs of nitrogen (154 × 10 9  g N yr −1 ) split roughly 60:40 between inorganic:organic components. Much of this was denitrified (34 × 10 9  g N yr −1 ) and buried (46 × 10 9  g N yr −1 ) within the estuarine system. A positive net annual ecosystem production for the bay further contributed to a large advective export of organic nitrogen to the shelf (91 × 10 9  g N yr −1 ) and negligible inorganic nitrogen export. Interannual variability was strong, particularly for the riverine nitrogen fluxes. In years with higher than average riverine nitrogen inputs, most of this excess nitrogen (50–60%) was exported from the bay as organic nitrogen, with the remaining split between burial, denitrification, and inorganic export to the coastal ocean. In comparison to previous simulations using generic shelf biogeochemical model formulations inside the estuary, the estuarine biogeochemical model described here produced more realistic and significantly greater exports of organic nitrogen and lower exports of inorganic nitrogen to the shelf. Key Points: A estuarine biogeochemical model was developed for Chesapeake Bay Interannually varying nitrogen fluxes were computed for 2001–2005 N export to the shelf was mostly organic, even when DIN input was high